Variación espacial y estacional de grupos funcionales de bacterias cultivables del suelo de un bosque tropical seco en México Spatial and seasonal variation of soil culturable-bacterial functional groups in a Mexican tropical dry forest - Noé Manuel Montaño; Ana Lidia Sandoval-Pérez; Maribel Nava-Mendoza; Juan Manuel Sánchez-Yañez; Felipe García-Oliva (Revista de Biología Tropical, 2013)
Los bosques tropicales secos tienen una amplia heterogeneidad ambiental y por lo tanto se podría esperar una variación temporal y espacial en la abundancia y tipo de grupos bacterianos activos. Se evaluó, durante dos años consecutivos, el efecto de la estacionalidad de la lluvia sobre algunos grupos bacterianos cultivables y nutrimentos del suelo en dos posiciones topográficas (crestas vs laderas) en el bosque tropical seco, Chamela Jalisco, México. La hipótesis fue que la variación temporal y espacial de la disponibilidad de recursos afectaría la abundancia de los grupos bacterianos funcionales (heterótrofas totales, celulolíticas, solubilizadores de fosfatos y nitrificantes) del suelo. En las crestas, el suelo fue más orgánico y con mayor concentración de nutrimentos totales y C orgánico lábil que en la ladera, registrando más bacterias heterótrofas y solubilizadoras de fosfato. En ambas posiciones topográficas la concentración de C y nutrimentos, así como el número de bacterias heterótrofas y solubilizadoras de P, decrecieron de la estación seca a la lluviosa en ambos años. En contraste, las bacterias nitrificantes fueron mayores en el suelo de la ladera, y al igual que las celulolíticas, tuvieron un patrón estacional opuesto a las bacterias heterótrofas, asociado a la disminución del C lábil y de la calidad de la materia orgánica. En conclusión, se sugiere que el relieve, la estacionalidad y la variación inter-anual de la lluvia regulan interactivamente la relación entre el C disponible y la estructura de las comunidades bacterianas del suelo en el bosque tropical seco de Chamela. Microbial biomass and activity in soils are frequently studied in tropical dry forests, but scarce information is available about the relationships between functional bacterial groups and soil fertility, where relief interacts with rainfall seasonality. The culturable-bacterial groups and nutrients were studied during two consecutive years in soils from two topographic areas of different relief (hilltop vs hillslope) in a tropical dry forest from Chamela Jalisco, Mexico. We expected that seasonal and spatial variation in soil resources availability affects the abundance of functional culturable-bacterial groups. To evaluate this, fifteen soil cores (1kg), 0-5cm depth, were taken in the dry, early rainy and rainy seasons, from each of the ten replicate plots in hilltop and hillslope areas located in three microbasins. We found that hilltop soils were more organic and had higher concentration of labile C and total nutrient forms than hillslope soils, for which these soils had higher counts of colony-forming units (CFU) of total heterotrophic and P solubilizing bacteria. In both hilltop and hillslope soils, C and nutrient concentrations, as well as the counts of CFU of heterotrophic and P solubilizing bacteria generally decreased from the dry to the rainy season during the two study years. In contrast, the counts of CFU nitrifying and cellulolytic bacteria were higher at the hillslope than at the hilltop soils. The seasonal pattern of both groups was opposite to that of heterotrophic bacteria, presumably associated with a decrease in soil labile C and organic matter quality. In conclusion, our study suggests that available C appears to be the main factor that controls the structure of soil bacterial groups and soil fertility, where relief, rainfall seasonality and intraand inter-annual variations are critical factors that interactively modify bacterial dynamics related to soil C availability in the tropical dry forest.